Gendered division of labor and women’s double burden: A Bourdieusian perspective on rural plantation work - Muhammad Arif Mustaqim (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
Gender inequality within the family is evident in the unequal division of labor, where women engaged in productive work continue to bear a double burden because domestic responsibilities remain primarily assigned to them. This study aims to analyze how women’s dual roles in the domestic and productive spheres within the plantation sector are formed and reproduced within rural gender structures. This study employs a qualitative interpretative approach through field research involving observation, interviews, and documentation. Data were analyzed inductively using Bourdieu’s theoretical framework and validated through triangulation and member checking. The findings show that: (1) women perform dual roles, remaining primarily responsible for domestic work while also engaging in productive labor in the plantation sector, whereas men remain positioned as the main breadwinners within rural gender structures; and (2) women’s productive work is reproduced through the interaction of patriarchal habitus, socio-cultural capital, and the social fields of the family and plantation, which continuously sustain gendered divisions of labor in rural life. The study concludes that women’s involvement in plantation work does not necessarily transform unequal gender relations. Women continue to bear a double burden, while patriarchal relations are reproduced through the interaction of habitus, capital, and social fields. Theoretically, this study contributes to Bourdieu’s perspective by demonstrating how internalized patriarchal dispositions contribute to the reproduction of gender inequality without direct coercion. Practically, it calls for critical gender education and village-level policies aimed at transforming internalized gender norms and promoting a more equitable distribution of domestic labor.